Penerapan Teknik Simulasi Dalam Layanan Bimbingan Kelompok Untuk Meningkatkan Rasa Percaya Diri Siswa Kelas X.F Di SMA Negeri 2 Mengwi Tahun Ajaran 2024/2025 - Zaini, Adjie Achmad; Suastini, Wayan (Universitas Muria Kudus, 2025)
This study aims to examine the implementation of simulation techniques in group guidance services to enhance students' self-confidence. The research was conducted in class X.F of SMA Negeri 2 Mengwi using classroom action research through two cycles. Data collection techniques included interviews, observation, and a closed-ended confidence scale. Initial observations revealed several students lacked confidence, such as hesitating to speak in front of the class and avoiding group interactions. After the implementation of simulation-based group guidance, there was a notable increase in students’ self-confidence scores-rising from an average of 57.6% to 74.8% across the two cycles. The findings suggest that structured simulations allow students to experience real-life scenarios in a safe environment, enabling them to build confidence and overcome social anxiety. The study concludes that simulation techniques in group guidance are effective in improving self-confidence among high school students.